Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Make c the subject:
x=-b+(b²-4ac) divided by 2a

The brackets mean square root


Sagot :

[tex]x=\dfrac{-b+\sqrt{b^2-4ac}}{2a}\\ 2ax=-b+\sqrt{b^2-4ac}\\ \sqrt{b^2-4ac}=2ax+b\\ b^2-4ac=(2ax+b)^2\\ -4ac=4a^2x^2+4abx+b^2-b^2\\ -4ac=4a^2x^2+4abx\\ c=-ax^2-bx[/tex]